2001
DOI: 10.1159/000045879
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and Diabetes mellitus

Abstract: In diabetes mellitus (DM), the urine flow rate is increased, and the fluid turnover in the body is accelerated because of the glucose-induced osmotic diuresis. On the other hand, plasma vasopressin (VP) is elevated in both type 1 and type 2 DM. This elevation seems to be due to a resetting of the osmostat. A high VP level is beneficial in the short term because it limits to some extent the amount of water required for the excretion of a markedly enhanced load of osmoles (mainly glucose). However, in the long r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(68 citation statements)
references
References 57 publications
4
62
0
2
Order By: Relevance
“…Thus, it is logical to hypothesize that the association between the effects of hyperglycemia may, at least in part, affect the occurrence of nocturia. In addition, the lack of arginine vasopressin (AVP) secretion and renal AVP resistance induced by diabetes may play a crucial role (20,21). People with obesity (BMI of > 27 kg/m 2 ) had higher odds for suffering from nocturia, as compared to those without obesity, which was consistent with numerous epidemiological studies (5,7,8,15,17).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, it is logical to hypothesize that the association between the effects of hyperglycemia may, at least in part, affect the occurrence of nocturia. In addition, the lack of arginine vasopressin (AVP) secretion and renal AVP resistance induced by diabetes may play a crucial role (20,21). People with obesity (BMI of > 27 kg/m 2 ) had higher odds for suffering from nocturia, as compared to those without obesity, which was consistent with numerous epidemiological studies (5,7,8,15,17).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, an imbalance in the relative abundance, sensitivity, affinity, and/or signal transduction of V2 versus V1a receptors in some disease states might alter the normal balance between V2 and V1a influences. Noteworthy, studies in rats have shown that V1a but not V2 receptors are downregulated (44,45) in situations in which vasopressin levels are increased, such as in diabetes (46). This study explored only the acute effects of V2 agonism and does not allow extrapolation to chronic situations, but a few experimental studies suggest that chronic V2 receptor-induced excessive sodium reabsorption could lead to sodium retention and to a compensatory rise in BP.…”
Section: Discussionmentioning
confidence: 99%
“…Type I diabetes has been associated with natriuresis and diuresis, as well as activation of vasopressin and the reninangiotensin-aldosterone system (7,84). Several groups have examined the regulation of sodium transporters in type I diabetic rodents (47,57,91,92,97,109,124).…”
Section: Altered Expression Of Sodium Transporter and Channels In Diamentioning
confidence: 99%